Citizenship education in building students' participatory attitudes towards HIV/AIDS prevention - Sitohang, Dahlan (Institute of Computer Science (IOCS), 2024)
The aim of the research is to find out how Citizenship Education Learning can build student attitudes towards dealing with HIV/AIDS. The research subjects were students at the National College of Health Sciences. The research object is Citizenship Education. The method used by researchers in this research is the descriptive method. This research data collection technique was carried out through a process of observation, interviews and documentation. Citizenship education fosters good character values so that students can face problems wisely so that students are able to become agents in overcoming HIV/AIDS which is carried out through community service in the form of socialization both through social media and directly related to the causes and negative impacts. caused. In developing students' civic disposition in tackling HIV/AIDS, student commitment is needed, building a culture of literacy in the campus environment so that the risks caused by HIV/AIDS are clear and maximizing existing legal regulations so that people feel afraid of committing violations of prostitution behavior.